Biochemical characterization of the YBPCI miniprotein, the first carboxypeptidase inhibitor isolated from Yellow Bell Pepper (Capsicum annuum L) : A novel contribution to the knowledge of miniproteins stability - Cotabarren, Juliana (2018)
The cystine-knot metallocarboxypeptidase inhibitors (MCPIs) are peptides that contribute to control proteolytic activity, involved in storage, growth and maintenance of plants. Lately studies reported several MCPIs with potential use in biomedical applications; as anti-cancer, anti-thrombotic, anti-malaric and anti-angiogenic agents. We report the isolation, purification, chemical stability and biochemical characterization of a novel carboxypeptidase A inhibitor (YBPCI) isolated from Capsicum annuum L. var. Yellow Bell Pepper, the first cystine-knot miniprotein (CKM) of the species. We demonstrate the stability of YBPCI (IC50 = 0.90 μg/ml) to high temperatures, high salt concentration and extreme pH values. MALDI-TOF/MS analysis detected a molecular weight of 4057 Da, and peptide mass fingerprint resulted in no matches with other protease inhibitors. In vitro gastrointestinal digestion subjecting YBPCI to pH 2 incubation and proteolytic attack resulted in complete inhibitory activity. To summarize, there are no reports to date of carboxypeptidase inhibitors in C. annuum species, giving our report much more relevance.